Intravenous Haloperidol Versus Ondansetron for Cannabis Hyperemesis Syndrome (HaVOC): A Randomized, Controlled Trial - Ruberto, Aaron J.; Sivilotti, Marco L.A.; Forrester, Savannah; Hall, Andrew K.; Crawford, Frances M.; Day, Andrew G. (Annals of emergency medicine, 2021)
Little is known about the cause or optimal treatment of hyperemesis in habitual cannabis users. Anecdotal evidence supports the use of haloperidol over traditional antiemetics for this newly recognized disorder. We compare haloperidol with ondansetron for cannabis hyperemesis syndrome. We randomized cannabis users with active emesis to either haloperidol (with a nested randomization to either 0.05 or 0.1 mg/kg) or ondansetron 8 mg intravenously in a triple-blind fashion. The primary outcome was the reduction from baseline in abdominal pain and nausea (each measured on a 10-cm visual analog scale) at 2 hours after treatment. Although the trial allowed for crossover, the primary analysis used only the first treatment period because few subjects crossed over. We enrolled 33 subjects, of whom 30 (16 men, aged 29 years [SD 11 years] using 1.5 g/day [SD 0.9 g/day] since age 19 years [SD 2 years]) received at least 1 treatment (haloperidol 13, ondansetron 17). Haloperidol at either dose was superior to ondansetron (difference 2.3 cm [95% confidence interval 0.6 to 4.0 cm]; P=.01), with similar improvements in both pain and nausea, as well as less use of rescue antiemetics (31% versus 59%; difference –28% [95% confidence interval –61% to 13%]) and shorter time to emergency department (ED) departure (3.1 hours [SD 1.7] versus 5.6 hours [SD 4.5]; difference 2.5 hours [95% confidence interval 0.1 to 5.0 hours]; P=.03). There were 2 return visits for acute dystonia, both in the higher-dose haloperidol group. In this clinical trial, haloperidol was superior to ondansetron for the acute treatment of cannabis-associated hyperemesis. The efficacy of haloperidol over ondansetron provides insight into the pathophysiology of this now common diagnosis in many EDs.